1996
DOI: 10.1007/bf00357678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan fasting on platelet aggregation in healthy male subjects

Abstract: The purpose of this study was to examine platelet aggregation during Ramadan fasting. A group of 20 healthy non-smoking male volunteers were studied, whose mean age was [21 (SD 2.4) years range 19-24]. The average fast was about 15 h. Venous blood samples were taken on 4 different days; 1 day before Ramadan (day 0), then on the 1st, 14th and 28th day of Ramadan. On each of these 4 days, blood samples were taken at 4 p.m. (1 h before the evening meal). Body mass index and platelet count did not change during fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Platelet count remained constant but platelet response to aggregating agents such as ADP, collagen and adrenaline dropped towards the end of Ramadan. 31 In conclusion, Ramadan fasting is a healthy method for improving the CHD risk profile. Since many factors can influence the effects of Ramadan fasting on biochemical and physiologic parameters (such as diet, daily activity, sleep pattern, the season of fasting, socio-economic factors,geography and climate), we recommend large-scale coordinated multi-centre studies, with standardized methodology, to explore the issue more extensively.…”
Section: Discussionmentioning
confidence: 95%
“…Platelet count remained constant but platelet response to aggregating agents such as ADP, collagen and adrenaline dropped towards the end of Ramadan. 31 In conclusion, Ramadan fasting is a healthy method for improving the CHD risk profile. Since many factors can influence the effects of Ramadan fasting on biochemical and physiologic parameters (such as diet, daily activity, sleep pattern, the season of fasting, socio-economic factors,geography and climate), we recommend large-scale coordinated multi-centre studies, with standardized methodology, to explore the issue more extensively.…”
Section: Discussionmentioning
confidence: 95%
“…These increases may be relevant to CHD as previous prospective studies suggest that CHD risk is approximately 70% greater in those having higher plasma D -dimer levels [5,16,17] . Aybak et al [18] showed that Ramadan fasting led to a decrease in the platelet responses to different aggregating agents. On the other hand, an increase in bleeding and coagulation time (but not above the physiologic limits) had been shown by the same study.…”
Section: Discussionmentioning
confidence: 99%
“…When the circadian variation of glucose blood levels was determined with the blood sampling done every 2 h (except in the time of sleep which was from 2: 00 to 8: 00 h), the results showed that this parameter increased at 2: 30 and 8: 00 h and decreased at 17: 30 h. The 24-hour mean decreased during Ramadan in comparison to the control day before the fasting [27] . Another study, where the blood samples were taken at 16: 00 h both before and during Ramadan, confi rmed the decrease in the afternoon blood glucose [28] .…”
Section: Meals and Energy Intake And Body Weight During Ramadanmentioning
confidence: 99%
“…Moreover, the platelet count [50] and responses to different aggregation agents decreased, leading to an increase in bleeding and coagulation time [28,55,56] . Antithrombin III also decreased in the morning and in the afternoon [56] .…”
Section: Hematological Changesmentioning
confidence: 99%
See 1 more Smart Citation